Gameplayowe transgresje w grach cyfrowych - Kochanowicz, Rafał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The latest and increasingly sophisticated digital simulations, often set in fantastical worlds, have become like laboratories in which players/ audiences can test their knowledge of culture, their ethical beliefs, interpretive skills, and anthropological imaginations. The article looks at games not just through the lens of their programmed poetics, but rather as laboratories in which experimentation becomes one of the elements of play, and gameplay touches the essence of the game – the activity, which is defined as dynamic competition within an adopted convention. One example of such experimentation is the transgressive way of conducting gameplay. However, creating a detailed typology of all possible transgressive gameplay is clearly not feasible, especially when taking into account accidental situations, such as when a player exploits a loophole or error in the programmed process without realizing that they are intentionally bypassing solutions designed by the creators. Nonetheless, intentional actions can be characterized in terms of three basic aspects – ingression (e.g., interference with computer programs), progression (e.g., fastrun, bypassing, etc.), and regression (transpositions, refunctionalizations, etc.). They concern both evidence of specific intentions and reveal ways of breaking rules, introducing one’s own rules, or forcing one’s own gameplay style.